THE PRACTICE OF USING THE MATHEMATICAL MODEL OF THE ARTIFICIAL NEURAL NETWORK IN THE CURRENT FORECASTING OF THE TAX BASE OF THE REPUBLIC (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2025)
The article proposes a method that allows using the capabilities of neural networks to predict the tax base of the republic. This method is suitable for developing a positive short-term forecast. This forecast creates the possibility of making predictions in an intelligent mode, taking into account time series.
Keywords: tax base; forecasting; artificial neural network; time series; tax administration; information system; expert system